(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This article explores methods and strategies for achieving equivalence in translating Khaled Hosseini’s The Kite Runner. By analyzing key linguistic, cultural, and emotional nuances of the text, the study provides insights into maintaining the integrity and impact of the novel in translation. Emphasis is placed on dynamic equivalence, cultural adaptation, and the challenges of representing Afghan culture.